Hubungan antara Kompetensi Sosial Guru dan Minat Belajar Siswa Kelas X (Sepuluh) pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) di MAN 2 Kota Bogor” - Ratu Balqis Sholiha; Sri Nurul Milla; Hilman Hakiem (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
The background of the problem in this study, namely the low interest in learning of class X (Ten) students in learning Islamic cultural history (SKI) at MAN 2 Bogor City, this research aims to find out whether there is a